Diamond Light Source: status and perspectives - Materlik, Gerhard (Philos Trans A Math Phys Eng Sci, 2015)
Diamond Light Source, a third-generation synchrotron radiation (SR) facility in the UK, celebrated its 10th anniversary in 2012. A private limited company was set up in April 2002 to plan, construct and operate the new user-oriented SR facility, called in brief Diamond. It succeeded the Synchrotron Radiation Source in Daresbury, a second-generation synchrotron that opened in 1980 as the world's first dedicated X-ray-providing facility, closing finally in 2008, by which time Diamond's accelerators and first beamlines were operating and user experiments were under way. This theme issue of Philosophical Transactions of the Royal Society A gives some examples of the rich diversity of research done in the initial five years, with some glimpses of activity up to 2014. Speakers at the 10 year anniversary symposium were drawn from a small number of major thematic areas and each theme was elaborated by a few speakers whose contributions were placed into a broader context by a leading member of the UK academic community in the role of rapporteur. This introduction gives a summary of the design choices and strategic planning of Diamond as a coherent user facility, a snapshot of its present status and some consideration of future perspectives.